Daptomycin plus fosfomycin versus daptomycin monotherapy in treating MRSA: protocol of a multicentre, randomised, phase III trial. Issue 3 (11th March 2015) - Shaw, E; Miró, J M; Puig-Asensio, M; Pigrau, C; Barcenilla, F; Murillas, J; Garcia-Pardo, G; Espejo, E; Padilla, B; Garcia-Reyne, A; Pasquau, J; Rodriguez-Baño, J; et al.
Abstract : Introduction: Despite the availability of new antibiotics such as daptomycin, methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia continues to be associated with high clinical failure rates. Combination therapy has been proposed as an alternative to improve outcomes but there is a lack of clinical studies. The study aims to demonstrate that combination of daptomycin plus fosfomycin achieves higher clinical success rates in the treatment of MRSA bacteraemia than daptomycin alone. Methods and analysis: A multicentre open-label, randomised phase III study. Adult patients hospitalised with MRSA bacteraemia will be randomly assigned (1:1) to group 1: daptomycin 10 mg/kg/24 h intravenous; or group 2: daptomycin 10 mg/kg/24 h intravenous plus fosfomycin 2 gr/6 g intravenous. The main outcome will be treatment response at week 6 after stopping therapy (test-of-cure (TOC) visit). This is a composite variable with two values: Treatment success: resolution of clinical signs and symptoms (clinical success) and negative blood cultures (microbiological success) at the TOC visit. Treatment failure: if any of the following conditions apply: (1) lack of clinical improvement at 72 h or more after starting therapy; (2) persistent bacteraemia (positive blood cultures on day 7); (3) therapy is discontinued early due to adverse effects or for some other reason based on clinical judgement; (4) relapse of MRSA bacteraemia before the TOC visit; (5) death for any reason before the TOC visit. Assuming a 60% cure rate with daptomycin and a 20% difference in cure rates between the two groups, 103 patients will be needed for each group (α:0.05, ß: 0.2). Statistical analysis will be based on intention to treat, as well as per protocol and safety analysis. Ethics and dissemination: The protocol was approved by the Spanish Medicines and Healthcare Products Regulatory Agency (AEMPS). The sponsor commits itself to publishing the data in first quartile peer-review journals within 12 months of the completion of the study. Trial registration number: NCT01898338.